A systematic approach on service life prediction of a model aerostat envelope. (July 2017) - Chatterjee, Upashana; Patra, Shantanu; Butola, Bhupendra S.; Joshi, Mangala
Abstract: Lighter-than-air (LTA) helium aerostats are receiving renewed attention for scientific as well as defense applications. Designing of new and improved materials for this kind of structure that consistently survive in the harsh atmospheric condition is one of the critical issues. However, durability of a newly developed material, in the actual field of application, is often unknown. Field experiments to know about its service life take prolonged time. In this study, a systematic approach has been proposed to predict the in service weatherability of a model aerostat envelope. A reliability model with two stress types (UV radiation and temperature) has been achieved to predict the service life of a model aerostat envelope material concerning the gas permeability through the material. Accelerated aging tests at higher stress levels have been performed to obtain a life stress relationship from which service life of the material has been determined at the use level conditions. Validation of the proposed model has also been performed using the actual field test data. It will be worthy to apply this approach in various fields of application to predict the service life of newly developed materials before their commercialization.